Effectiveness of governance towards digitalisation at eThekwini Metropolitan Municipality in KwaZulu-Natal province, South Africa - Nirmala Govender; Purshottama S. Reddy (Africa’s Public Service Delivery & Performance Review, 2019)
Background: South African cities have been facing challenges since democratisation to meet the expectations of the citizens. The challenges have included fraud and corruption, financial constraints, lack of service delivery and technological progress, amongst others, which were underpinned by weak leadership and governance processes. This article explored eThekwini Metropolitan Municipality’s technological progress and identified that inefficiencies in good governance and the lack of a governance framework have limited digitalisation.